FEATURES OF ORGANIZING THE WORK OF TOURISM INFLUENCERS IN UKRAINE - SENKIV, MARIANA; KYIANYTSIA, MARIYA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The paper examines in detail the theoretical foundations of the influencer activities. It was found out that influencer activity is the leading form of education and advertising in the 21st century and can be described as an industry effort that tries to promote products to raise brand awareness through content disseminated by social media users who are considered influential. The process of digitalization as the main prerequisite for the development of influencer activities is analyzed. Approaches to the understanding and features of the work of tourism influencers are considered. The tourisml industry is one of those niches that are heavily influenced by influencer activities. Tourism influencers of Ukraine in the 21st century are very important. They work mostly on such online platforms as Instagram and YouTube. The level and characteristics of digitalization, structure of the market of tourism influencers’ activities and features of their work in Ukraine, are studied. The most popular Ukrainian tourism influencers travel a lot around the world, but some devote a lot of time to exploring their home country, looking for unique places and tourist attractions. Usually the main goal of their blogs is to popularize Ukrainian places that are still unknown to the average tourist. Problems and prospects of the organizing of the activities of tourism influencers in Ukraine are defined, and recommendations for improving their work are developed. All influencers in Ukraine are not protected or regulated by law. There is also the problem of the lack of correct terminology used in relation to the influencers. Already now, new social media are becoming popular among younger generation, so Ukrainian tourism influencers should use these platforms in their work.
Keywords: tourism; influencer; digitalization; Instagram; YouTube; Ukraine